PENERAPAN STRATEGI BELAJAR PREVIEW, QUESTION, READ, REFLECT, RECITE, REVIEW (PQ4R) TERHADAP HASIL BELAJAR BIOLOGI SISWA KELAS X SMAN 4 PADANG - Nanda, Prima; Armen, Armen; Indriati, Gustina (STKIP PGRI Sumbar, 2013)
ABSTRACT Low learning outcomes at biology of students are caused by many factors , such as lack of student motivation to read and understand the material in learning biology , students tend to be passive in learning and teaching is dominated by the lead teacher resulting student learning outcomes is still below the minimum completeness criteria defined by school. One solution that can be done to overcome these problems is to use learning strategies preview, question, read, reflect, Recite, review ( PQ4R ). This study aims to look at the application of learning strategies PQ4R on learning outcomes at biology of class X student of SMAN 4 Padang school year 2012/2013.This study was conducted in April-May. Experiment with this type of research study design randomized Only Control Group Design. The study population was all class X SMAN 4 Padang. Sampling was done by purposive sampling, whereas the control determination of class and class control done by lottery, so we get the X4 as class experiment with the number of students 32 and X1 as an experimental class control by the number of students 32. The instrument used in this study is a test of student learning outcome. Based on the analysis results obtained by the average test results of the experimental study on class is 78.68 and standard deviation 9.63, while the average achievement test control class 74.46 and standard deviation 7.17. The data obtained were analyzed using t-test. Based on the analysis of data in the form of hypothesis testing performed, obtained t = 2 t-table = 1.645. Therefore t > t- table, then the hypothesis is accepted, it means that the learning outcomes of students in learning biology is becoming more increases. Application of learning strategies PQ4R has positive effects on learning outcomes at biology of class X student SMAN 4 Padang school year 2012/2013.